Result of extracorporeal irradiation and re-implantation for malignant bone tumors: A review of 30 patients - Olarn Arpornchayanon (2018)
Aims: Extracorporeal irradiation and re-implantation (ECI) has been used as limb salvage surgery for musculoskeletal oncology patients. Biological reconstruction, no risk of disease transmission and immunological reaction, ready availability and preservation of bone stock are the major advantage of this surgical technique. This case series details the outcomes of ECI. Methods: In total, 30 patients (31 sites) were treated with ECI between 1996 and 2007. The mean survivor follow-up period was 47 months (at least 24 and up to 108). The results of ECI were judged in terms of recurrence and limb function. Surgical failure was defined as local recurrence and the need for amputation, and reoperation for any reasons. Functional status was assessed by three functional assessment systems: Mankin score, the Musculoskeletal Tumor Society score (MTSS) and the Toronto Extremity Salvage score (TESS). Results: In all, 24 patients (80%) were alive and free from disease at last follow up. Operative failure occurred in two cases (7%) and the main complication was infection in three cases (10%). The mean values of the MTSS and the TESS were 82% (57-98%) and 81% (57-99.), respectively. Excellent or good results were achieved in 27 patients (90%) according to the Mankin score. Patients classified as stage IA and IIA, upper extremity and ECI-prosthesis composite, mostly demonstrated excellent results without any complications. Conclusion: Our results are encouraging in terms of the orthopedic and oncological outcomes. This indicates that ECI offers a good alternative method for reconstruction in limb salvage surgery. © 2012 Wiley Publishing Asia Pty Ltd.